(untitled) (Perner’s Contacts, 2009)
Electronics tolls cost are important hauliers cost. This article analyzes to development of toll for road networks using in some of Europes states: Germany, Czech Republic, Austria, Poland,Hungary, Belgium, Netherlands, Luxemburg, Sweden, Denmark and Switzerland. The article analyzes to development and volume of tolling in Slovak Republic.